faktor-faktor yang berhubungan dengan pendokumentasian asuhan keperawatan di RSUD NOONGAN. - Drova Grano Manorek; Adrian Umboh; Aaltje Manampiring (Jurnal Kesehatan Medika Saintika, 2021)
ABSTRACTNursing care documentation is very important and needs to be considered because what is done must be recorded and what is recorded is what is done to help the process of nursing care to patients. The purpose of this study was to examine the factors associated with documenting nursing care at the Noongan Regional Hospital. The number of respondents was 59 people. The activity starts with signing the agreement, filling out the questionnaire and filling out the observation sheet. The research method used quantitative data with aapproach cross sectional. Data were analyzed by univariate, bivariate, and multivariate using Chi-square and logistic regression analysis test. Based on thetest chi square to see the relationship between the independent and dependent variables, it was found that the p value for each independent variable was age (p = 0.775), gender (p = 0.740), level of education (p = 0.000) and supervision of the head of the room (p. = 0,000). The results of the logistic regression test showed that the variable with the highest OR value was the supervision of the head of the room (OR = 41.074). The conclusion of this study is the variables that have a relationship with nursing care documentation, namely the level of education and supervision of the head of the room, the variables that have no relationship are age and gender, and the variable that has the strongest influence is the supervision of the head of the room. The hospital, can carry out training for the head of the room in increasing supervision and for nurses in improving nursing care documentation.Keywords: Nursing care; documenting; factors.